Low vigorous physical activity is associated with increased adrenocortical reactivity to psychosocial stress in students with high stress perceptions. (June 2017) - Gerber, Markus; Ludyga, Sebastian; Mücke, Manuel; Colledge, Flora; Brand, Serge; Pühse, Uwe
Highlights: High stress combined with low vigorous physical activity (VPA) is associated with increased adrenocortical stress reactivity. High stress combined with low VPA is associated with less positive affect during the Trier Social Stress Test. This is one of the first studies in which survey-based and experimental methods are combined. Physical activity was assessed objectively and categorization was based on internationally accepted standards. Abstract: Objectives: The pathways by which physical activity impacts on participants' health are still not fully understood. The purpose of the present study was to go beyond existing research by combining methods from survey-based and experimental stress research, and by examining whether the potential of vigorous physical activity (VPA) to attenuate physiological and psychological stress responses is moderated by participants' subjective stress perception. Methods: The sample consisted of 42 undergraduate students ( M = 21.2 ± 2.2 years, 52% women). Participants self-reported their stress and wore an accelerometer device for seven consecutive days. To examine differences in the adrenocortical, autonomic and psychological stress reactivity, salivary free cortisol, heart rate, state anxiety, mood and calmness were assessed prior to, during and after the Trier Social Stress Test (TSST). The cut-offs of the American College of Sports Medicine (ACSM) were used to distinguish between students below/above current VPA recommendations. Results: High levels of perceived stress combined with VPA levels below the ACSM's standards (<3 × 20 min/week) were associated with an increased salivary cortisol response to the TSST ( p < .05). No significant group differences existed for heart rate. However, students with high stress/low VPA experienced less favourable affect throughout the entire testing session ( p < .05). Conclusions: Our study suggests that VPA has a high stress-protective potential among undergraduate students with high stress levels. Our findings highlight that promoting VPA in young adults seems to be a promising strategy to increase physiological and psychological stress resilience.